Corporate Governance Practices in India: An Empirical Study - Chauhan, Shikha; Sharma, Reema (Gyan Management Journal, 2008)
The concept of corporate governance has become very much essential in today’s business world. It basically deals with the problems which arise due to separation of ownership and control of companies. To protect the interests of inves.ting public, SEBI has amended the listing agreement by inserting clause 49 which made it mandatory for companies to follow corporate governance guidelines. The recommendations made by the committee were divided into mandatory and non- mandatory categories. This paper examines the corporate governance practices of some selected companies in India. A sample of 15 listed companies has been taken on random basis for a period of 6 years from 2001-02 to 2006-07. The data with respect to governance variables have been collected from the Prowess database and annual reports of the companies.